Kenya’s blue rebalancing after the Somalia v. Kenya maritime delimitation judgment: a strategic toolkit for restoring leverage - Sun, Jie (Frontiers in Political Science, 2025)
The October 2021 ruling by the International Court of Justice (ICJ) on the Kenya-Somalia maritime boundary dispute significantly undermined Kenya’s strategic and economic interests. This policy brief proposes a non-militarized toolkit to help Kenya regain leverage. The toolkit combines legal innovation through the exploitation of ambiguities in the United Nations Convention on the Law of the Sea (UNCLOS), economic statecraft via the issuance of blue sovereign bonds, and narrative reframing that consistently highlights Somalia’s governance failures. By leveraging regional alliances and multilateral partnerships, Kenya can mitigate the adverse impacts of the ruling, safeguard its maritime interests, and assert its leadership in regional maritime governance without escalating tensions. This approach offers a replicable model for smaller states navigating territorial disputes in the wake of unfavorable legal rulings.